2007
DOI: 10.1002/macp.200700015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(lauryl acrylate) by Single‐Electron Transfer/Degenerative Chain Transfer Living Radical Polymerization Catalyzed by Na2S2O4 in Water

Abstract: Living radical polymerization of lauryl acrylate was achieved by SET/DTLRP in water catalyzed by sodium dithionite. The work describes the synthesis of a highly hydrophobic and polar monomer in aqueous medium. The plots of $\overline M _{\rm n}$ versus conversion and ln[M]0/[M] versus time are linear, indicating a controlled polymerization. This method leads to α,ω‐diiodopoly(lauryl acrylate)s that can be further functionalized. The MWDs were determined using a combination of three detectors: RALLS, DV, and RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…To vary the polymerization method, a promising environmental friendly route to poly(lauryl acrylate) was proposed by using single-electron transfer/degenerative chain transfer living radical polymerization (SET/DTLRP). 219 The polymerization was catalyzed by Na2S2O4 and was conducted in aqueous media. In this way, α,ω-diiodo-poly(lauryl acrylate) was obtained which can be further used as a macro-initiator.…”
Section: Iv7 Poly(alkylacrylate)s/poly(alkylmethacrylate)smentioning
confidence: 99%
“…To vary the polymerization method, a promising environmental friendly route to poly(lauryl acrylate) was proposed by using single-electron transfer/degenerative chain transfer living radical polymerization (SET/DTLRP). 219 The polymerization was catalyzed by Na2S2O4 and was conducted in aqueous media. In this way, α,ω-diiodo-poly(lauryl acrylate) was obtained which can be further used as a macro-initiator.…”
Section: Iv7 Poly(alkylacrylate)s/poly(alkylmethacrylate)smentioning
confidence: 99%
“…It is observed that on grafting the paper exhibits a less noticeable fibrillary structure. Both, polymers pLA and pOA present glass transition temperatures below room temperature, thus they are in a rubber state, and their chains are mobile enough to promote the fiber aggregation through multiple chain entanglement. These observations agree with previous reports of acrylic polymers grafted from cellulose fibers in paper sheets …”
Section: Resultsmentioning
confidence: 99%
“…(Figure 6a (i)) that act as TPEs (Figure 6a (ii)) [89]. A copolymer of LAc and SAc has been chosen as the midblock of the triblock copolymers as these monomers offer a number of advantages, including low glass transition temperatures [90,91] and long alkyl side chains that are highly hydrophobic and provide greater resistance to degradation [92]. Varying the length of the side chain on the polyacrylate midblock (C18 and C12 in stearyl and lauryl acrylate repeat units, respectively) is a convenient tool for tuning the physical properties of the triblock copolymers.…”
Section: Poly(α-methylene-γ-butylrolactone)-poly(menthide)-poly(α -Mementioning
confidence: 99%